2007
DOI: 10.1065/lca2007.05.330
|View full text |Cite
|
Sign up to set email alerts
|

Individual adaptation of industry LCA practice: Results from two case studies in the Swedish forest products industry

Abstract: Prior Research on LCA PracticePrior research on LCA provides few clear answers on what shapes LCA practice in industry. LCA methodology has been the focus of most of the research done to date. Research on the application of the tool in industry is limited and provides divergent results. AbstractGoal, Scope and Background. The mere existence of life cycle assessment (LCA) methodology and general acceptance of the life cycle philosophy is not enough to make their use widespread in industry. To gain a better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A social science perspective on LCM has, for example, been proposed as a way of explaining “how,” in addition to “what” LCM is and is performed (Hoffman, 2003). Such studies have shown that identical recommendations for implementation of LCA and LCM becomes inapplicable, as organizations differ and translate these guidelines differently (see, e.g., Baumann, 2000; Heiskanen, 2000; Rex & Baumann, 2007).…”
Section: Lcm and Its Management In Organizationsmentioning
confidence: 99%
“…A social science perspective on LCM has, for example, been proposed as a way of explaining “how,” in addition to “what” LCM is and is performed (Hoffman, 2003). Such studies have shown that identical recommendations for implementation of LCA and LCM becomes inapplicable, as organizations differ and translate these guidelines differently (see, e.g., Baumann, 2000; Heiskanen, 2000; Rex & Baumann, 2007).…”
Section: Lcm and Its Management In Organizationsmentioning
confidence: 99%
“…The studied practitioners worked in various environmentally related positions, such as environmental or sustainability managers, LCA specialists, and LCM project managers. This material was initially collected as part of separate studies of MNCs and their use of the LC approach (Baumann 2000;Rex and Baumann 2004;Rex and Baumann 2006;Rex 2007;Nilsson-Lindén et al 2018;Rex et al 2015). This present paper thus presents a secondary analysis building on a re-use of pre-existing qualitative data derived from previous research studies in order to investigate additional research questions (see Heaton 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of LC adoption and integration of LCM in company practices have been relatively few and more studies have been called for (Seuring 2004;Vermeulen and Seuring 2009). Existing studies show that LCM development requires more efforts than adoption: LCM has to be adapted and tailored to the specific organizational context (Mortimer 2011;van der Heijden et al 2012; Sonneman and Margni 2015); Baumann (2000) observed that LC practitioners engaged in LC promotional activities and concluded that identical LC implementation 'recipes' will not fit all organizations (Baumann 2000); individuals' interpretations and contextual factors influence the use of LCA in organizations (Heiskanen 2000;Rex and Baumann 2007). In sum, the significance of practitioners for LCM development is identified in these papers, but their role is not examined in detail.…”
Section: The Role Of Lc Promoters For Adoption and Adaptation Of Lcm mentioning
confidence: 99%
“…So far, LCA has already been applied to evaluate the environmental impact of different wood products (Rex and Baumann 2007). Recent publications on LCA have studied wood products such as paper and pulp (Dias et al 2007a;González-García et al 2009a), boards (Rivela et al 2006a(Rivela et al , 2007González-García et al 2009b, 2011a, floor coverings (Petersen and Solberg 2004;Nebel et al 2006), window frames (Richter and Gugerli 1996;Asif et al 2002;Tarantini et al 2011), walls (Werner 2001), furniture (Taylor and van Langenberg 2003), containers (González-García et al 2011b), chairs (Fet et al 2009), writing paper (Lopes et al 2003) and packaging materials (Farreny et al 2008) as well as the use of wood wastes in ephemeral architecture (Rivela et al 2006b).…”
Section: Framework Of Forest Operations In Lca Studies (State Of Art)mentioning
confidence: 99%